1999
DOI: 10.1046/j.1365-2850.1999.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Something always comes up’: nurse–patient interaction in an acute psychiatric setting

Abstract: In this study, 10 nurses and 10 patients were interviewed to explore factors influencing nurse-patient interactions in an acute psychiatric inpatient facility. The six themes that emerged from the nursing interviews were; environment, something always comes up, nurses' attributes, patient factors, instrumental support and focus of nursing. The four themes from the patient interviews were; nurses' attributes, role perceptions, clinical care, and time. These findings have implications for clinical practice, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 21 publications
2
73
1
3
Order By: Relevance
“…Psychiatric nurses have reported performing unnecessary routines including completing paperwork for personnel and billing and making duplicative documentation (Higgins, Hurst, & Wistow, 1999). Further, the lack of resources such as secretarial support increased nurses' administrative workloads, resulting in a decreased amount of time available for nurse-client interactions (Cleary, 2004;Cleary & Edwards, 1999;Fourie, McDonald, Connor, & Barlett, 2005;Higgins et al, 1999). In summary, psychiatric nurses must engage in various activities while maintaining patient safety and a therapeutic milieu.…”
Section: Activity and Workload On An Inpatient Psychiatric Unitmentioning
confidence: 99%
“…Psychiatric nurses have reported performing unnecessary routines including completing paperwork for personnel and billing and making duplicative documentation (Higgins, Hurst, & Wistow, 1999). Further, the lack of resources such as secretarial support increased nurses' administrative workloads, resulting in a decreased amount of time available for nurse-client interactions (Cleary, 2004;Cleary & Edwards, 1999;Fourie, McDonald, Connor, & Barlett, 2005;Higgins et al, 1999). In summary, psychiatric nurses must engage in various activities while maintaining patient safety and a therapeutic milieu.…”
Section: Activity and Workload On An Inpatient Psychiatric Unitmentioning
confidence: 99%
“…The extant literature related to inpatient psychiatric nurses was conducted in Australia and New Zealand (Berg & Hallberg, 2000;Cleary, 2004;Cleary & Edwards, 1999;Delaney, Clearly, Jordan, & Horsfall, 2001;Farrell & Dares, 1999;Fourie, McDonald, Connor, & Barlett, 2005;Happell, Martin, & Pinikahana, 2003;O'Brien & Cole, 2004;Taylor & Barling, 2004), Canada (Robinson, Clements, & Land, 2003), England (Callaghan, 1991;Fagin, Brown, Bartlett, Leary, & Carson, 1995;Fagin et al, 1996;Hall, 2004;Higgins, Hurst, & Wistow, 1999;Mistral, Hall, & McKee, 2002;Sammut, 1997;Sullivan, 1993;Whittington, 2002;Whittington & Wykes, 1992), Norway (Severinsson & Hummelvoll, 2001), Sweden (Severinsson & Hallberg, 1998), Japan (Ito, Eisen, Sederer, Yamada, & Tachimori, 2001), and a combination of two or more of the above countries (Melchior, Bours, Schmitz, & Wittich, 1997;Thomsen, Arnetz, Nolan, Soares, & Dallender, 1999).…”
Section: Nurse Practice Environmentmentioning
confidence: 99%
“…Other nurses reported that they did not feel safe in their work environment (Poster & Ryan, 1994;Sammut, 1997). Furthermore, the lack of other types of resources such as secretarial support increased nurses' administrative workload resulting in a decreased amount of time available for nurse-client interactions (Cleary, 2004;Cleary & Edwards, 1999;Fourie et al, 2005;Higgins et al, 1999). In sum, staffing is a critical factor that can potentially influence the outcome of a physical restraint episode.…”
Section: Nurse Practice Environmentmentioning
confidence: 99%
“…For example, Emlyn talked about the size of his CMHN's caseload and Sian showed her awareness that her CMHN had many other patients to see. Service user accounts included several references to mental health nurses who were 'too busy', which is echoed in other studies about mental health nursing (Cleary & Edwards, 1999;Stenhouse, 2011), reinforcing the notion that nurses' one to one time spent with patients was limited.…”
Section: Nursing Work: Task Focused and Time-limitedmentioning
confidence: 89%
“…For example, the chaos and crisis of acute admission environments is highlighted by researchers (Deacon, 2003;Deacon et al, 2006), as nurses are reported as having to continually prioritise and reprioritise their work due to persistent demands. There is perhaps an expectation from staff that 'Something always comes up', which is how Cleary and Edwards (1999) titled their paper about the continual interruptions to nurses' planned activities in acute settings. Although at the time of interview Laura was employed in a nursing home, she had been placed on at least five wards during her student experience, and had background knowledge of inpatient environments.…”
mentioning
confidence: 99%